PENDIDIKAN ZERO TOLERAN DALAM IBADAH - Agus, Agus (PMPP Lembaga Penelitian dan Studi Kebijakan, 2023)
This study discusses the interpretation of Q.S. al-Kafirun in general verses one to six with a tarbawi approach. In language al-Kafirun means unbelievers. They are people who reject and close themselves from the light of truth of Islam as the religion of rahmatan lil'alamin. Islam is a religion that upholds tolerance. Tolerance is an attitude of openness and acknowledging differences, both ethnicity, language, skin color, culture, and religion because this is the sunatullah, which is sometimes misinterpreted by equating religions moreover justifying the ways and practices of worship of other religions. Islam recognizes the term tasamuh, namely harmony between religious communities or in Arabic it means mutual permission, facilitating each other. The purpose of this study is to provide answers to the question of how we as Muslims behave towards non-Muslims, the limits of tolerance between religious communities in order to create harmonious and peaceful relations. This study was written qualitatively using the literature review method to obtain descriptive data in the form of words. The results are expected that this study will become one of the references in obtaining information and attitudes of tolerance between religious communities. The conclusion that can be drawn is that Islam is a religion that is rahmatan lil'alamin, full of peace, and highly upholds the value of tolerance, there is no compulsion in believing in Islam but as a Muslim it is obligatory to spread and call for belief in Allah as the only god that must be worshiped